Nail gun penetrating injury of the heart mimicking an acute coronary syndrome - Comoglio, Chiara (Springer-Verlag, 2010)
We describe the case of a 75-year-old man admitted to hospital for chest pain and syncope. Physical examination was normal with evidence of a very small wound on the left chest. Considering the presence of multiple coronary risk factors, an acute coronary syndrome was initially suspected, but the electrocardiogram (EKG) was normal and only a slight increase of cardiac enzymes was detected. The hypothesis of aortic dissection was also considered and in order to discriminate between the aortic and coronary syndrome, a thoracic and coronary computed tomography (CT) scan was performed. The CT scan showed a metallic structure, suggestive of a nail, about 6 cm in length, in the deep layers of the left ventricular wall and a small pneumothorax due to a lung lesion. The patient was therefore transferred to our department for urgent cardiac surgery that was performed without complications.